Adenocarcinoma of the esophagogastric junction: relationship between clinicopathological data and p53, cyclin D1 and Bcl-2 immunoexpressions - Lehrbach,Dárcio Matenhauer (2009)
CONTEXT: Esophagogastric junction adenocarcinoma has an aggressive behavior, and TNM (UICC) staging is not always accurate enough to categorize patient's outcome. OBJECTIVES: To evaluated p53, cyclin D1 and Bcl-2 immunoexpressions in esophagogastric junction adenocarcinoma patients, without Barrett's esophagus, and to compared to clinicopathological characteristics and survival rate. METHODS: Tissue sections from 75 esophagogastric junction adenocarcinomas resected from 1991 to 2003 were analyzed by immunohistochemistry for p53, cyclin D1 and Bcl-2 using streptavidin-biotin-peroxidase method. The mean follow-up time was 60 months SD = 61.5 (varying from 4 to 273 months). RESULTS: Fifty (66.7%) of the tumors were intestinal type and 25 (33.3%) were diffuse. Vascular, lymph node and perineural infiltration were verified in 16%, 80% and 68% of the patients, respectively. The patients were distributed according to the TNM staging in IA in 4 (5.3%), IB in 10 (13.3%), II in 15 (20%), IIA in 15 (20%), IIIB in 15 (20%) and IV in 16 (21.3%). Immunohistochemical analysis was positive for p53, cyclin D1 and bcl-2 in 68%, 18.7% and 100%, respectively. There was no association between immunoexpression and vascular and/or perineural invasions, clinicopathological characteristics and patients' survival rate. CONCLUSION: In this selected population, there was no association between the immunomarkers, p53, cyclin D1 and bcl-2 and clinicopathological data and/or overall survival.